Origins of the European economy communications and commerce, A.D. 300-900 - McCormick, Michael 1951- (Cambridge University Press, 2001)
For fifty years debate has raged about early European commerce during the period between antiquity and the middle ages. Was there trade? If so, in what - and with whom? New evidence and new ways of looking at old evidence are now breaking the stalemate. Analysis of communications - the movements of people, ideas and things - is transforming our vision of Europe and the Mediterranean in the age of Charlemagne and Harun al Rashid. This is the first comprehensive analysis of the economic transition during this period for over sixty years. Using new materials and new methodology, it will attract all social and economic historians of antiquity and the middle ages, and anyone concerned with the origins of Europe, the history of the slave trade, medicine and disease, cross-cultural contacts, and the Muslim and Byzantine worlds
Keywords: Geschichte 300-900; Geschichte; Wirtschaft; Fernhandel; Europa; Europe / Commerce / History; Europe / Economic conditions / To 1492